Chemoradiotherapy-induced Cochlear Toxicity (International Journal of Scientific Research and Management (IJSRM), 2019)
Radiation-induced sensorineural hearing loss (RI-SNHL) is a progressive and irreversible complication of radiotherapy (RT) or chemoradiotherapy (CRT) of brain or head and neck tumors. Onset and progression times of RI-SNHL may broadly vary depending on the RT technique, dose, and concurrent or adjuvant usage of ototoxic medications, such as cisplatin. Characteristically the high frequencies (≥4 kHz) form the first affected range on a typical audiogram, which may be trailed by impairements in the lower hearing frequencies. RI-SNHL may adversely impact both the academic and social advancement in pediatric age and may deteriorate quality of life measures in all affected patients regardless of their age. Even if not eliminate all, in absence of a unequivocally proven medical treatment to avoid or alleviate the RI-SNHL, utilization of more advanced RT techniques, such as the intensity-modulated RT, and limiting the cochlea doses to ≤40-45 Gy for RT alone,<10 Gy for concurrent RT and cisplatin, and <10-12 Gy for stereotactic radiosurgery applications may demonstrate valuable in minimizing the risk of SNHL development. Furthermore, as reactive oxygen species (ROS) are the essential introductory causatives in RT-induced damage via activating the apoptotic cascade in cochlear hair cells, hopefully the development of novel radioprotective agents with the ability to lessen ROS production may prove beneficial in reducing the cochlear damage, and therefore, RI-SNHL, in near future.